CRTC1 enhances PD-L1-mediated tumor immunosuppression in non-small cell lung cancer via the Notch1/Akt signaling pathway - Feng, Xujun; Shi, Yuan; Yuan, Fang; Hu, Yanxia; Tang, Xiangdong; Zhang, Wei; Gan, Jiadi; Sun, Longhua; Cao, Lingling (Frontiers in Immunology, 2025)
BackgroundWhile programmed death-ligand 1 (PD-L1)-targeted immunotherapy represents an advancement in non-small cell lung cancer (NSCLC), patient outcomes remain suboptimal. Aberrant activation of the cyclic adenosine monophosphate (cAMP) response element binding protein (CREB)-regulated transcription coactivator (CRTC) is linked to malignant proliferation and functionality in lung cancer cells. This study investigates the involvement of CRTC1 in tumor immunity.MethodsCRTC1 and Notch1 expression were regulated in A549 and NCI-H1299 NSCLC lines through plasmid-mediated overexpression/silencing to assess their effects on cell viability, apoptosis, migration, and invasion. CRTC1/Notch1-dysregulated Lewis lung carcinoma (LLC) cells were co-cultured with T cells to evaluate T cell activation and function. The efficacy of combined CRTC1 knockdown/overexpression and atezolizumab (anti-PD-L1) was tested in an LLC xenograft mouse model.ResultsCRTC1 promoted cell viability, migration, and invasion while suppressing apoptosis across NSCLC models. In LLC cells, CRTC1 upregulated tumor cell PD-L1 expression, suppressed T cell-derived IFN-γ and IL-2 production, diminished endogenous CXCL10/11 secretion, and impaired T cell proliferation and cytotoxicity. Mechanistically, CRTC1 interacted with Notch1 to activate the Notch1/Akt pathway, stimulating PD-L1 upregulation, thereby facilitating tumor immunosuppression and growth. Notably, CRTC1 overexpression reversed the protective effects of atezolizumab on tumor growth. Combining CRTC1 knockdown with atezolizumab synergistically enhanced anti-tumor T cell immunity, achieving the most significant tumor regression in xenografts.ConclusionThese findings indicate that CRTC1 in tumor cells suppresses PD-L1-mediated anti-tumor immunity and promotes tumorigenesis via the Notch1/Akt signaling axis. Dual targeting of CRTC1 and PD-L1 demonstrates therapeutic synergy, suggesting CRTC1 pathway inhibition could optimize immunotherapy outcomes in NSCLC patients.